ParaFlow: Fine-grained parallel SDN controller for large-scale networks - Song, Ping; Liu, Yi; Liu, Chi; Qian, Depei (Journal of network and computer applications, 2017)
Using Software-Defined Networking (SDN), the flexibility and programmability of networks can be significantly increased through the decoupling of the control and data planes. However, network scale-up in large-scale data centers can rapidly increase the computational complexity of operations such as the shortest path calculation on the network topology or Quality-of-Service (QoS) routing, which, in turn, can cause scalability problems in current SDN controllers. This paper proposes ParaFlow, a multithreaded SDN controller that supports fine-grained parallelism by exploiting application parallelism and utilizing multi-/many-core resources to accelerate event processing. ParaFlow also provides a flow-based programming interface that allows application developers to program with network flows rather than various types of low-level events. Experimental results show that ParaFlow achieves satisfactory performance and scalability in the multithreaded case.